Heat adaptation improves viability of Lactococcus lactis subsp. lactis HE-1 after heat stress - Kang, Chang-Ho; Jeon, Haneul; Shin, YuJin; Kwon, Yoon-Jung; So, Jae-Seong (Food science and biotechnology, 2015)
We have studied the potential of environmental adaptation as a survival mechanism to enable lactic acid bacteria to withstand spray drying. The formulation process of these bacteria exposes them to stresses such as heating and dehydration on daily basis. In the present study, the effect of heat adaptation on subsequent exposure of Lactobacillus lactis subsp. lactis HE-1 cells to various types of lethal stress was examined by comparing the viability of heat-adapted cells with nonadapted ones. The responses of heat-adapted cells to other environmental stresses such as H 2 O 2 , heat, acid, and ethanol were also examined. The results showed that heat-adapted cells had a higher survival rate than the non-adapted cells. Morphological analysis was performed to explain the observed differences. The adaptation mechanisms in response to stresses in L. lactis subsp. lactis HE-1 are to be fundamental for survival during spray drying process.